Nature in the poetry of Ibn Zamrak Al-Gharnati (Journal of Human Sciences, 2024)
Nature dominated the poetry of Andalusians in general. There is hardly a poet’s collection that does not contain descriptions of nature, singing of its beauty, and fascination with its beauty. Nature poetry does not stop at the purpose of description only, but we see it present in all poetic purposes. Because the poets of Andalusia were influenced by the beauty of its captivating nature, its picturesque composition, and the manifestations of civilization and architecture prevailing throughout it. The poets of Granada had their abundant share of descriptive poetry. Granada combined the picturesque nature that captivates the mind, and the cultural richness represented by the splendor of buildings, including palaces, houses, squares and roads. Despite the poets’ fascination with the beauty of Andalusia, they were not at the same level in the art of description. There were those who dominated descriptive poetry and mixed with most of its purposes, and among these was Ibn Zamrak, who is considered one of the most prominent poets of description as a whole. This study will attempt to shed light on the art of describing nature in this poet’s poetry, and document it in detail.This study came in four directions:1.Political, social and cultural life in the Kingdom of Granada in the era of the poet.The life and poetry of Ibn Zamrak.Nature in Gharnatic poetry.4. Description of nature, both silent and living, in Ibn Zamrak’s poetry.